EFEKTIFITAS TERAPI SPA KAKI DALAM MENURUNKAN KELUHAN NEUROPATI DIABETIK PADA PASIEN DIABETES MELLITUS - Mona Hastuti (Jurnal Maternitas Kebidanan, 2020)
Indonesia is facing diabetes mellitus disease as a pandemic global, which Indonesia is standing at 6thrank with population of the country has the most diabetes mellitus patients at the age of 20 to 79 in the world and is expected to increase by the time (IDF 2017). Peripheral vascular and sensory to motor neuropathy disease are the highest complications of diseases and frequently found in diabetes mellitus case. Diabetik foot spa is one of the therapies to boost patient’s blood circulation also provide a relax feeling for patient’s feet, therefore this activities aims to observe the effectiveness of diabetik foot spa treatment to the patients of diabetes mellitus to minimize diabetik neuropathic. This study used a quasi-experimental research design with pretest-posttest techniques, took action in two groups, the intervention group and Kontrol group, each group consist of 25 samples in 4 weeks of observation period at “Puskesmas Sunggal”. Found that there was a significant point result on the Paired Samples t-test pretest-posttest test with p value= 0.000 at the 0.05 level for the intervention group in the comparison result before action and after and on the other hand in the Kontrol group was found p value result with 0.587 at the 0.05 level. This study shows that respondents who were given the diabetik foot spa in the intervention group had better feeling and sensation after than before the treatment were given to the patients